Disasters and mental health: evidence from the Fundao tailing dam breach in Mariana, Brazil - Matsunaga, Liz (2020)
This paper investigates mental health consequences of Fundao dam rupture, in Mariana, Brazil, in 2015. Unlike previous studies that analyze the affected region as a unit, we investigate each affected region separately hence accounting for heterogeneous effects due to the vast spectrum of the disaster. We use a difference-in-differences framework to investigate mental disorders hospitalizations and use the approach of Ferman e Pinto (2019) to correct our standard errors estimations due to the few number of treated units in each affected group. We show a sizable effect in mental disorders hospitalizations in Minas Gerais state, especially at municipalities located near Fundao dam (upstream Candonga reservoir). Our estimations indicate that the disaster induced at least a two-fold increase in mental disorders hospitalizations in this region with considerable impacts in a broad set of mental disorders. We also find effects for municipalities in Minas Gerais state located downstream Candonga reservoir (a four-fold increase in hospitalizations due to disorders with onset on childhood and adolescence) and indirectly affected ones (a two-fold increase in stress-related hospitalizations). Finally, we bring evidences of the late and persisting effects of the disaster in mental health, with an increased number of hospitalizations persisting (if not starting) years after the dam collapsed.